How Online Reviews and Ratings Buffer the Negative Effects of FOMO in Consumer Decision-Making (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
This research examines the psychological and behavioral aspects of consumers affected by Fear of Missing Out (FOMO) in online shopping settings, with particular attention to how online ratings and reviews influence purchasing decisions. FOMO can lead to impulsive buying behaviors, often fueled by social pressure, urgency, and the perception of limited-time offers or product scarcity. The study aims to understand how consumers engage with and interpret user reviews and ratings to manage the cognitive and emotional impact of FOMO during their decision-making process. Using a qualitative approach, data were collected through semi-structured interviews and focus group discussions involving participants who had recently made online purchases influenced by FOMO. Thematic analysis revealed that while numerical ratings often act as a preliminary screening tool, it is detailed, visually supported, and contextually relevant reviews that play a more critical role in alleviating doubts, reinforcing purchase confidence, and encouraging more rational decision-making. Participants frequently placed greater trust in authentic, experience-based reviews rather than generic star ratings, which were often perceived as easily manipulated or lacking depth. Additionally, the study highlights that the credibility and trustworthiness of user-generated content significantly affect how consumers evaluate online information in high-pressure situations. Ultimately, the findings suggest that online reviews can serve as a psychological support system, helping consumers cope with emotional stress and complexity associated with FOMO. These insights hold valuable implications for digital marketers and e-commerce platforms aiming to optimize their review systems, improve transparency, and foster trust-based relationships with consumers in an increasingly competitive and emotionally charged digital marketplace.